Life‐history trade‐offs during the seed‐to‐seedling transition in a subtropical wet forest community. (22nd November 2012) - Muscarella, Robert; Uriarte, María; Forero‐Montaña, Jimena; Comita, Liza S.; Swenson, Nathan G.; Thompson, Jill; Nytch, Christopher J.; Jonckheere, Inge; Zimmerman, Jess K.; Zuidema, Pieter
Summary The transition from seed to established seedling (STS) represents a major bottleneck in plant demography with implications for community dynamics and the maintenance of species diversity. The relative strength of seed limitation versus seedling establishment limitation can reveal life‐history trade‐offs that contribute to the maintenance of community diversity. If seed limitation dominates, chance arrival to open sites may play a key role in maintaining diversity. If seedling establishment limitation dominates, however, species relative abundances may depend more on tolerance to environmental and biotic conditions during seedling establishment (i.e. species‐specific regeneration niche). We used three years of seed rain and seedling recruitment data for 19 species of tropical woody plants collected in the Luquillo Forest Dynamics Plot in Puerto Rico to (i) examine a trade‐off between seed and seedling establishment limitation and (ii) quantify the biotic and abiotic factors that mediate the STS transition. We did not find evidence of a life‐history trade‐off in the form of a negative correlation between seed and seedling establishment limitation. However, species varied considerably in the relative levels of seed and seedling establishment limitation they displayed. Seed mass correlated negatively with seedling establishment limitation but not with seed limitation. We found striking differences in STS transition between life‐forms categorized as trees (including two palms) and lianas; lianas exhibited significantly higher STS transition rates than trees. The biotic and abiotic variables most strongly associated with successful STS transition differed between life‐forms. For trees, conspecific seed density and temporal fruiting concentration had negative effects on seedling establishment, while seed mass had a positive effect. A significant interaction between leaf litter input at a plot and seed size suggested that large‐seeded species had higher STS transition probability in plots with more leaf litter biomass. This effect was reversed for small‐seeded species. For lianas, leaf litter had a negative effect on STS transition and temporal fruiting concentration had a positive effect. Synthesis. Our analyses demonstrate the multidimensional axes of regeneration niches and how they can be related to seed size. Long‐term data sets are critical for understanding these relationships because the relevant factors vary along large spatial and temporal scales.